Comparing the Expression of Olfaction-Related Genes in Gypsy Moth (Lymantria dispar) Adult Females and Larvae from One Flightless and Two Flight-Capable Populations - Clavijo McCormick, Andrea; Grosse-Wilde, Ewald; Wheeler, David; Mescher, Mark C.; Hansson, Bill S.; De Moraes, Consuelo M. (Frontiers in Ecology and Evolution, 2017)
In insects, flight and sophisticated olfactory systems go hand in hand and are essential to survival and evolutionary success. Females of many Lepidopteran species have secondarily lost their flight ability, which may lead to changes in the olfactory capabilities of both larval and adult stages. The gypsy moth, Lymantria dispar, an important forest pest worldwide, is currently undergoing a diversification process with three recognized subspecies: the Asian gypsy moth (AGM) L. dispar asiatica, the Japanese gypsy moth L. dispar japonica (JGM) and the European gypsy moth (EGM) L. dispar dispar. Females of EGM populations from North America have lost their flight capacity whereas the JGM and AGM females are flight capable, making this an ideal system to investigate the relationship between flight and olfaction. We used next-generation sequencing to obtain female antennal and larval head capsule transcriptomes in order to (i) investigate the differences in expression of olfaction-related genes among populations; (ii) identify the most similar protein sequences reported for other organisms through a BLAST search, and (iii) establish the phylogenetic relationships of these sequences with respect to other insect species. Using this approach, we identified 115 putative chemosensory genes belonging to five families of olfaction-related genes. A principal component analysis revealed that the gene expression patterns of female antennal transcriptomes from different subspecies were more similar among them than to the larval head capsules of their respective subspecies supporting strong chemosensory differences between the two developmental stages. An analysis of the shared and exclusively expressed genes for three populations shows no evidence that loss of flight affects the number or type of genes being expressed. These results indicate either that (a) loss of flight does not impact the olfactory gene repertoire or that (b) the secondary loss of flight in the American EGM populations may be too recent to have caused major changes in the genes being expressed. However, we found higher expression values for IRs, OBPs GRs and ORs in EGM females, suggesting that differences in transcription rates could be an adaptation of flightless females to their chemical environment. Differences in olfactory genes and their expression in the